On projecting the distribution of private households by size - Dalkhat M. Ediev (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2007)
The paper introduces a general approach to distributing households by size, which is based on recurrent procedure of estimating conditional proportions of households of a given size among households with the same or larger size. Based on formal study and on empirical evidence, models and methods are proposed for deriving the distribution of households from their average size. The methods are tested and compared using census data and projections of Austrian and EU households. The approach proposed is also developed to distribute households both by size and by socio-demographic characteristics of the household head. Methods proposed are consistent and robust and may find a wide range of applications in household modelling and projecting, in enriching household projections by headship rates and other extrapolative methods, and also in studying the economic, ecological and other implications of household dynamics.
Keywords: 300; House modelling; household projection; headship rates; distribution by size; distribution by age of household head; Privater Haushalt; Räumliche Verteilung; Haushaltsökonomik; Österreich; EU-Staaten